1975
DOI: 10.1128/iai.11.6.1252-1260.1975
|View full text |Cite
|
Sign up to set email alerts
|

Association of Streptococcus mutans with Human Dental Decay

Abstract: The association of Streptococcus mutans with human dental decay was investigated by using several types of samples: (i) paraf'fin-stimulated saliva samples taken from children with from 0 to 15 decayed teeth; (ii) pooled occlusal and approximal plaque taken from children with no decayed or filled teeth, or from children with rampant caries of 10 or more teeth; (iii) plaque removed from single occlusal f'issures that were either carious or noncarious. The results showed a significant association between plaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
2
2

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(147 citation statements)
references
References 43 publications
7
133
2
2
Order By: Relevance
“…In the present study the increment of lactobacilli (for reviews see 7,21). The cor-caries in schoolchildren has been corresponding salivary factors are the related with the above factors and the aim secretion rate, the pH and the buffer of the investigation was to find out if any capacity (for a review see 22).…”
mentioning
confidence: 80%
“…In the present study the increment of lactobacilli (for reviews see 7,21). The cor-caries in schoolchildren has been corresponding salivary factors are the related with the above factors and the aim secretion rate, the pH and the buffer of the investigation was to find out if any capacity (for a review see 22).…”
mentioning
confidence: 80%
“…As in other types of coronal dental decay, the main bacteria implicated in ECC are of the group now termed "mutans streptococci" of which the species S. inutans and S. sobrims are the most commonly isolated in human dental caries (51,52). There is an abundance of evidence showing the association of mutans streptococci in the initiation as well as in the progression of dental caries in animals (2, 53,54) and humans (8, 55,56). Mutans streptococci are the principal bacteria isolated from children with ECC (7, 57-62).…”
Section: Mutans Streptococcimentioning
confidence: 99%
“…Whereas AgP is associated with Aa, it is well established that dental caries is caused by the gram-positive group of microorganismsmutans streptococci (ms) (Loesche, 1986), as well as other cariogenic bacteria (Becker et al, 2002;Piwat et al, 2010). The Aa colonize and survive on the oral mucosa, the tooth surface, and in the subgingival domain (Henderson et al, 2003), while Sm is found more in the supragingival biofilm (Loesche et al, 1975 andLoesche, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the microbiological sampling of whole saliva can be used to detect the presence of both Aa, in spite of the fact that its main habitat is the subgingival biofilm, and Sm, which can be usually found in supragingival biofilm (Loesche et al, 1975;Lindquist et al, 1989;Umeda et al, 1998;Cortelli et al, 2005).…”
Section: Discussionmentioning
confidence: 99%